A Bibliometric Analysis of Digital Image Forensics. Issue 1 (2nd January 2020) - Gokhale, Angelina; Mulay, Preeti; Pramod, Dhanya; Kulkarni, Ravi
ABSTRACT: We present a bibliometric analysis of the evolving field of digital image forensics (DIF) from 2014 to early 2020. The study analyses and discusses the results obtained from the highly indexed Scopus database for various subject areas, renowned authors, funding agencies, and affiliations using a mind map approach. We adapt the PRISMA methodology formerly applied for systematic reviews to refine our search results. The results of this study indicate an increasing awareness of DIF in countries like China, India, and Italy along with an increase in publications since 2018, specifically, with the application of deep learning techniques for DIF.